Effect of Nickel Doping on Interfacial Reaction between Lead-free Solder and Ni-P Substrate - Siti Rabiatull Aisha, Idris; Saliza Azlina, Osman; Ali, Ourdjini (Trans Tech Publications, Switzerland, 2012)

(untitled)
Due to environmental concern, lead-free solder are taking the place of eutectic Sn-Pb solder in electronic packaging industry. Among various lead free alloys, Sn–Ag–Cu (SAC) alloys are leading lead-free candidate solders for various applications because it is offered better properties. This study investigates the interfacial reactions during reflow soldering and isothermal aging between Sn-3.0Ag-0.5Cu (SAC305) and Sn-3.0Ag-0.5Cu-0.05Ni (SACN30505) on electroless nickel/immersion palladium/immersion gold (ENEPIG) surface finish. The substrates were subjected to isothermal aging at 125˚C for up to 2000 hours with solder size diameter of 500µm. The results indicated that after reflow soldering, (Cu, Ni)6Sn5 IMC is formed between solder and substrate while after aging treatment a new IMC was formed between (Cu, Ni)6Sn5 and substrate known as (Ni, Cu)3Sn4. Moreover, after soldering and isothermal aging, Ni-doped (SACN) solder represents a thicker IMC compared to SAC solder. Aging time of solder joints results in an increase of IMC’s thickness and changes their morphologies to become more spherical, dense and with larger grain size. In addition, the results also revealed that the thickness of intermetallics formed is proportional to the aging duration.